2020
DOI: 10.1017/s0007485320000267
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis and screening of detoxification-related genes in an amitraz-resistant strain of Panonychus citri

Abstract: Panonychus citri (McGregor) is the most common pest in citrus-producing regions. Special low-toxicity acaricides, such as spirocyclic tetronic acids and mite growth inhibitors, have been used for a long time in China. However, pesticide resistance in mites is a growing problem due to the lack of new acaricide development. Wide-spectrum insecticides, such as amitraz have gained acceptance among fruit growers. An amitraz-resistant strain of P. citri was obtained by indoor screening to examine field resistance mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…At the level of the metabolic process, an insecticide can increase the rate of metabolism of another co‐administered insecticide. For example, in Carnolian honeybee workers ( Apis mellifera carnica ), sublethal concentrations of thymol caused an increase in the activity of the enzymes acetylcholinesterase (AChE) and glutathione S‐transferase (GST) (Glavan et al, 2020), while in an amitraz‐resistant strain of the citrus pest Panonychus citri , an increase in the expression of AchE was recorded by Real‐time PCR technique, indicating that this enzyme could be involved in the hydrolysis of amitraz (Yu et al, 2020). Additional studies should be conducted to determine if the enzyme AchE is involved in the metabolization of amitraz in T. infestans nymphs.…”
Section: Discussionmentioning
confidence: 99%
“…At the level of the metabolic process, an insecticide can increase the rate of metabolism of another co‐administered insecticide. For example, in Carnolian honeybee workers ( Apis mellifera carnica ), sublethal concentrations of thymol caused an increase in the activity of the enzymes acetylcholinesterase (AChE) and glutathione S‐transferase (GST) (Glavan et al, 2020), while in an amitraz‐resistant strain of the citrus pest Panonychus citri , an increase in the expression of AchE was recorded by Real‐time PCR technique, indicating that this enzyme could be involved in the hydrolysis of amitraz (Yu et al, 2020). Additional studies should be conducted to determine if the enzyme AchE is involved in the metabolization of amitraz in T. infestans nymphs.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the ED value of EVM0004493 (1.55) gene is greater than EVM0003193 (1.41), which implies that the former has a stronger association with resistance trait. Previous genetic analysis of resistance indicated that multiple genes may be involved in the resistance of P. citri to amitraz, 74 so we cannot ignore the influence of other mutant genes in the candidate interval on the susceptibility of mites to amitraz, such as ABCC10 (EVM0006133) and transmembrane channel‐like protein (EVM0009492) etc . located on contig00033, which have a certain role in the transportation of heterologous compounds or ions.…”
Section: Discussionmentioning
confidence: 99%
“…A sufficient number of hybrid progenies (F) were transferred to the feeding device for culture. Based on a previous study, 74 the mites in the device were sprayed with 100 mg/L amitraz solutions. After 24 h, the dead mites were considered to be susceptible to amitraz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Panonychus citri (Acarina:Tetranychidae) is a spider mite with worldwide distribution and causes large economic losses in many countries [1,2]. The P.citrus has a stabbing mouthpiece and feeds on the juice from the leaves, shoots, ower buds, and fruits of Citrus [2,3].Currently, the main strategy for P.citrus control remains chemical control, however it has developed strong tolerance for many acaricides, such as pyridaben, fenpyroximate [4,5]. Therefore, it is necessary to select more effective insecticides for controlling this pest.…”
Section: Introductionmentioning
confidence: 99%